Musical text: An effective instrument in teaching language and culture. Issue 3 (1st October 2020) - McIntire, Amy Marie
Abstract: Studying musical text effectively reinforces grammar structures and vocabulary taught in class while simultaneously developing cultural literacy, a critical component in second language acquisition. Musical text facilitates a multimodal learning experience as it combines the verbal and aural modes, and is often accompanied by the visual mode. In addition, studies have shown that there is a strong connection between music, visual mental imagery and memory, which is beneficial for language learning. What is unique to the study of musical text is that there is sound, and sound has meaning. In tone languages, a change in pitch changes word meaning, while intonation and phonology influence meaning in non-tone languages. Voice code, experiential meaning potential and provenance further assist in conveying the meaning of the text. Whether using music as a complement to reinforce topics introduced in traditionally structured language courses or as the basis for an entire syllabus of university level language study, the following case studies demonstrate that musical text can be a powerful instrument in enhancing language acquisition not only for children, but also in the context of higher education.